Comparative efficacy of minoxidil alone versus minoxidil combined with low-level laser therapy in the treatment of androgenic alopecia: a systematic review and meta-analysis - Abdulmajeed Alosaimi; Abdullah Algarni; Abdulrahman Alharbi; Abdulmalik Alotaibi; Abdullah Alomairi; Mohannad Alsurayhi; Waleed Alharbi (Journal of Dermatological Treatment)
Objective This systematic review evaluates the efficacy of minoxidil alone versus minoxidil with low-level laser therapy (LLLT) for androgenic alopecia.Study design systematic review and meta-analysis.Methods An online search of PubMed, Web of Science, and MEDLINE was conducted. Randomized clinical trials comparing minoxidil monotherapy with minoxidil and LLLT combination therapy were included based on predefined criteria. The Risk of Bias 2.0 (RoB 2.0) tool was used for quality assessment.Results From 38 identified studies, 34 remained after excluding 4 duplicates. Further exclusions left 4 eligible studies comparing minoxidil alone with minoxidil and LLLT. The meta-analysis found no statistically significant differences in hair counts between the two groups at baseline, 12 weeks, and 8 weeks post-treatment [mean difference = −0.04, 95% CI −1.22 to 1.14, p = .95, I² = 0%]. Similarly, hair diameter showed no significant differences at the same time points [mean difference = 0.00, 95% CI −0.00 to 0.00, p = .98, I² = 38%].Conclusion The combination of minoxidil and LLLT does not significantly improve outcomes compared to minoxidil alone for treating androgenic alopecia.